Task-Involving Motivational Climate and Enjoyment in Youth Male Football Athletes: The Mediation Role of Self-Determined Motivation - Amaro, Nuno (2023)
Background: This study aimed at examining the mediation role of self-determined motivation (identified and integrated regulation and intrinsic motivation) in the association between task-involving climate and enjoyment in youth male football athletes. Methods: A total of 109 youth males (M = 14.38; SD = 1.55) were recruited to participate in this study. The survey included sociodemographic data and validated instruments such as the Motivational Climate Sport Youth Scale, the Behavioral Regulation Sport Questionnaire, and the Sports Enjoyment Scale. Results: The results showed that the task-involving climate was a positive and significant predictor of integrated regulation and intrinsic motivation. In addition, integrated regulation and intrinsic motivation were positive and significant predictors of enjoyment. The results of the mediation analysis revealed a partial mediation role of self-determined motivation in the relationship between task-involving climate and enjoyment. Significant indirect effects only occurred through intrinsic motivation. Conclusions: Providing higher levels of enjoyment in the sport context could be an excellent option for leisure activities for children and youth, as long as self-determined motivation and task-involving climates provided by the coaches are present.